2022
DOI: 10.46827/ejel.v7i2.4226
|View full text |Cite
|
Sign up to set email alerts
|

Some Common Errors in Vietnamese-English Translation of English-Major Juniors at Tay Do University, Vietnam

Abstract: <p>Most Vietnamese students who learn English often make mistakes when learning Vietnamese-English translation because there are many differences between Vietnamese and English. Therefore, translation is a difficult subject when learning English. This research “Some common errors in the Vietnamese-English translation of English majors at Tay Do University” focused on some common errors of English majors in Vietnamese-English translation. In this research, the participants were 75 English majored juniors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Likewise, studies by Ly (2022) and Phan et al (2022) both revealed that the biggest challenges of English-majored students, from their perspective, were the lack of lexical resources, as well as their weak grammatical, syntactical, and semantical knowledge and skills.…”
Section: St-century Skills In Relation To Translation Competencementioning
confidence: 99%
“…Likewise, studies by Ly (2022) and Phan et al (2022) both revealed that the biggest challenges of English-majored students, from their perspective, were the lack of lexical resources, as well as their weak grammatical, syntactical, and semantical knowledge and skills.…”
Section: St-century Skills In Relation To Translation Competencementioning
confidence: 99%
“…By engaging with different languages, young learners gain insights into diverse cultures, fostering a more inclusive worldview (Arono & Nadrah, 2019;Hutahaean et al, 2023;Rahayu, 2021). This skill becomes increasingly valuable in our interconnected global society (Phan et al, 2022;Simanjuntak, 2019).…”
Section: Introductionmentioning
confidence: 99%